Our only world : ten essays - Berry, Wendell, 1934- (Counterpoint, 2015)
"In this new collection of [ten] essays, Berry confronts head-on the necessity of clear thinking and direct action. Never one to ignore the present challenge, he understands that only clearly stated questions support the understanding their answers require. For more than fifty years we've had no better spokesman and no more eloquent advocate for the planet, for our families, and for the future of our children and ourselves"--